Directional solidification, nanoindentation and thermionic properties of LaB6(100)-ZrB2 eutectic composite. Issue 6 (June 2022) - Yang, Xinyu; Deng, Chenhui; Gu, Zengjie; Shang, Jihua; Wang, Yan; Zhang, Jiuxing; Su, Haijun
Abstract: LaB6 (100)-ZrB2 eutectic composite was directionally solidified by optical floating melting zone at solidification rate V= 100 mm/h. It was shown that the stable eutectic growth can be achieved by periodic diverging and convergent growth, indicating that eutectic spacing was not unique value, but existed a limited range under a given rate. The atoms of the LaB6 (100)/ZrB2 interface were directly bonded. The mechanical property of the individual eutectic phase was evaluated by the nanoindentation. Both average Berkovich hardness and elastic modulus of LaB6 /ZrB2 phases was higher than that of LaB6 phase. Thermionic emission of DS LaB6 (100)-ZrB2 eutectic obeyed the Longo theory, indicating only the metal ceramic of LaB6 matrix in the composite emitted the electron. The practical work function distribution of DS LaB6 (100)-ZrB2 eutectic composite ranged from 2.51 to 3.18 eV, and the lowest work function was located around the LaB6 /ZrB2 interface, where had the highest current density